Возведем обе части в квадрат:
![(\sqrt{101}+\sqrt{102})^{2} = 101+2\sqrt{10302}+102=203+2\sqrt{10302} (\sqrt{101}+\sqrt{102})^{2} = 101+2\sqrt{10302}+102=203+2\sqrt{10302}](https://tex.z-dn.net/?f=%28%5Csqrt%7B101%7D%2B%5Csqrt%7B102%7D%29%5E%7B2%7D+%3D+101%2B2%5Csqrt%7B10302%7D%2B102%3D203%2B2%5Csqrt%7B10302%7D)
![(\sqrt{99}+\sqrt{104})^{2}=99+2\sqrt{10296}+104=203+2\sqrt{10296} (\sqrt{99}+\sqrt{104})^{2}=99+2\sqrt{10296}+104=203+2\sqrt{10296}](https://tex.z-dn.net/?f=%28%5Csqrt%7B99%7D%2B%5Csqrt%7B104%7D%29%5E%7B2%7D%3D99%2B2%5Csqrt%7B10296%7D%2B104%3D203%2B2%5Csqrt%7B10296%7D)
(203+2\sqrt{10296})" alt="(203+2\sqrt{10302})>(203+2\sqrt{10296})" align="absmiddle" class="latex-formula">
Теперь очевидно, что
(\sqrt{99}+\sqrt{104})" alt="(\sqrt{101}+\sqrt{102})>(\sqrt{99}+\sqrt{104})" align="absmiddle" class="latex-formula">